Heavier, faster and less affordable cars: The consequence of EU regulations for car emissions - Tommaso Pardi (European Trade Union Institute (ETUI), 2022)
Between 1990 and 2019, the European transport sector was expected to reduce its CO2 emissions by 40 per cent to keep track with the 100 per cent CO2 reduction target on the 1990 level set by the European Commission for 2050. But, in fact, the transport sector has increased its CO2 emissions by 32 per cent during these last 30 years, with passenger cars representing 43 per cent of total CO2 emissions from the transport sector. This growing divergence between the historical trajectory of CO2 emissions of passenger cars in Europe and where they were supposed to go to reach carbon neutrality in 2050 is the main reason why the European automotive sector is now facing the most radical and potentially disruptive transformation of its history. Rapid and widespread electrification appears today as the only possible technological solution to reconcile this diverging path with the EU Green Deal. In the EU Green Deal the short-term objective is to reach, by 2030, a 55 per cent reduction in CO2 emissions (on 1990) in all economic sectors - the 'Fit for 55' package. For passenger cars the proposal made by the European Commission in 2021 foresees not only a 55 per cent reduction of the CO2 emissions of new cars by 2030 but a 100 per cent reduction by 2035. In other words, in slightly more than ten years, the internal combustion powertrain that has been at the core of this industry for more than a century, and which concentrates around 25 per cent of the value added and 40 per cent of the total employment of the European automotive industry, will be phased out. [...]
Keywords: 330; Treibhausgas-Emissionen; Kraftfahrzeug; EU-Recht; EU-Staaten